UNIFYING ECOLOGICAL AND EVOLUTIONARY DYNAMICS THROUGH EXPERIMENTAL STOCHASTIC DEMOGRAPHY - Smallegange, I; Coulson, T (2009)
Ecological and evolutionary dynamics depend upon variation in birth and death rates. Consequently characterizing birth and death rates, and identifying factors that explain variation in these rates, should be the foundation of population and evolutionary ecology. Given the central role of birth and death, it is perhaps surprising that relatively few population biologists apply the most recent demographic approaches to their research. This may be because demography is seen as little more than accounting, and therefore dull, or because stochastic demography is seen as mathematically challenging. It is our belief that ecologists and evolutionary biologists have much to gain through increased mastery of stochastic demography. Its applications could push forward our understanding of eco-evolutionary dynamics in stochastic environments, and the outcome could further the unification of ecology and evolution. In this essay we briefly explain why mastering demographic approaches should be a desirable objective for any evolutionary ecologist. We start by describing some aspects and insights gained through application of demographic methods, before suggesting an area where we believe application could prove insightful.